Media pembelajaran dalam prespektif islam - alfiah, nisa (Maliki Interdisciplinary Journal, 2025)
This artikel explores the role of learning media from an Islamic perspective, emphasizing its significance in enhancing the educational process. Learning media are crucial in facilitating knowledge acquisition and skill development, particularly in the current era, where education increasingly integrates technology. The study discusses various types of learning media, including audio, visual, and technological tools, and their alignment with Islamic teachings. It highlights Quranic and Hadith references that support the use of media in education. The research concludes that learning media not only improve learning effectiveness but also serve as a means to instill Islamic values. Integrating learning media within the framework of Islamic education can create a more engaging and meaningful learning experience for students.